Formation And Development Of Students' Cognitive Abilities In Engineering Graphics Training (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article discusses methods for the formation and development of cognitive abilities, metacognitive skills, cognitive interests, and self-regulation of students in teaching engineering graphics. Overcoming the difficulty in which a student experiences situational interest while completing a learning task.